Phosphoinositide 3-kinase signaling in the vertebrate retina - Rajala, Raju V. S. (The American Society for Biochemistry and Molecular Biology, 2010)
The phosphoinositide (PI) cycle, discovered over 50 years ago by Mabel and Lowell Hokin, describes a series of biochemical reactions that occur on the inner leaflet of the plasma membrane of cells in response to receptor activation by extracellular stimuli. Studies from our laboratory have shown that the retina and rod outer segments (ROSs) have active PI metabolism. Biochemical studies revealed that the ROSs contain the enzymes necessary for phosphorylation of phosphoinositides. We showed that light stimulates various components of the PI cycle in the vertebrate ROS, including diacylglycerol kinase, PI synthetase, phosphatidylinositol phosphate kinase, phospholipase C, and phosphoinositide 3-kinase (PI3K). This article describes recent studies on the PI3K-generated PI lipid second messengers in the control and regulation of PI-binding proteins in the vertebrate retina.